2013
DOI: 10.4103/0975-7406.120073
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of resin rich plant extracts

Abstract: Background:The in vitro antibacterial activity of resin rich methanolic extracts (RRMEs) of Commiphora myrrha, Operculina turpethum, and Pinus roxburghii.Materials and Methods:Different concentration were studied by agar-well diffusion method against Gram-positive (Staphylococcus aureus, Bacillus subtilis, Micrococcus luteus, Enterococcus faecalis) and Gram-negative bacterial strains (Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Shigella dysenteriae).Results:Among all the bacterial strains teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The abietic acids were stronger antibacterial agents than pimaric and labdane acids, and among the individual resin acids, dehydroabietic acid was generally the most potent (Shuaib, et al, 2013). Diterpene antimicrobial activity against certain microorganisms associated with the presence of the group in the molecule functional groups such as carboxyl, hydroxyl, aldehyde or ketone and among other groups.…”
Section: Resin / Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abietic acids were stronger antibacterial agents than pimaric and labdane acids, and among the individual resin acids, dehydroabietic acid was generally the most potent (Shuaib, et al, 2013). Diterpene antimicrobial activity against certain microorganisms associated with the presence of the group in the molecule functional groups such as carboxyl, hydroxyl, aldehyde or ketone and among other groups.…”
Section: Resin / Essential Oilsmentioning
confidence: 99%
“…Resin of P. ponterosa effective against Gram-positive bacteria Bacillus subtilis (ATCC 9372) and Brevibacterium ammoniagenes (ATCC 6872) with a paper disc method (Himejima et al, 1992). Shuaib et al (2013) reported that the resin of P. roxburghii showed better activity against Gram-positive than Gram-negative bacterial strains. Research conducted by Sipponen and Laitinen (2011) revealed that the pure resin of Picea abies significantly reduce the amount of bacteria inoculation (S. aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, and Candida albicans) within 24 hours.…”
mentioning
confidence: 99%
“…Also herbal medicines have been known to man for centuries (Almagboul et al, 1988;Michie and Cooper, 1991;Newall et al, 1996;Azaizeh et al, 2003;Hawar, 2008;Saadabi and Moglad, 2011;Gadir and Ahmed, 2014). Therapeutic efficacy of many oleo-gum resins for many disorders has been described by practitioners of traditional medicine (Wanner et al, 2010;Shuaib et al, 2013;Singh et al, 2013). Myrrh Commiphora myrrha has been used for centuries as incense and for medicinal purposes (Claeson et al, 1991;Michie and Cooper, 1991;Al-Harbi et al, 1997;Al Faraj, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported to have several medicinal importances, such as intestinal antiseptic, antidyslipidemic, and spasmolytic [2]. The wood, resin, gum, oil, seeds, needle, and bark from P. roxburghii have been used for the treatment of several diseases in many parts of the world [3]. Furthermore, it is the rich source of terpenoids, flavonoids, tannins, and xanthones [4].…”
Section: Introductionmentioning
confidence: 99%